Coronary artery spatial distribution of chronic total occlusions: Insights from a large US registry. Issue 1 (10th November 2016) - Garcia, Santiago; Alraies, M. Chadi; Karatasakis, Aris; Yannopoulos, Demetris; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Jaffer, Farouc A.; Yeh, Robert W.; Patel, Mitul P.; Bahadorani, John; Karacsonyi, Judit; Kalsaria, Pratik; et al.
Abstract : Objective: To assess the spatial distribution of chronic total occlusions (CTOs) within the coronary arteries and describe procedural strategies and outcomes during CTO percutaneous coronary intervention (PCI). Background: Acute occlusions due to plaque rupture tend to cluster within the proximal third of the coronary artery. Methods: We examined the clinical and procedural characteristics of 1, 348 patients according to lesion location within the coronary tree. Results: A total of 1, 369 lesions in 1, 348 patients (mean age 66 ± 10 years, 85% male) were included. CTO PCI of proximal segments ( n  = 633, 46%) was more common than of mid ( n  = 557, 41%) and distal segments ( n  = 179, 13%). Patients undergoing CTO PCI of proximal segments were more likely to be smokers ( P  < 0.01), have prior coronary artery bypass graft surgery ( P  = 0.03) and lower ejection fraction ( P  = 0.04). CTOs occurring in proximal segments had longer length ( P <0.01), proximal cap ambiguity ( P  < 0.01), and moderate/severe calcification ( P  < 0.01) compared to mid or distally located CTOs. Interventional collaterals were more often present in CTO PCI of proximal segments (64%, 53%, 56%, P  < 0.01) consistent with the higher use of retrograde approach (47%, 33%, 37%, P  < 0.01) relative to antegrade wire escalation (67%, 82%, 82%, P  < 0.01). Procedural complexity was higher in CTO PCI of proximal segments (vs. mid and distal): contrast volume= 275 ml (200–375), 260 ml (200–350), 250 ml (175–350), P  = 0.01; fluoroscopy time 53 minutes (32–83), 39 minutes (24–65), 40 minutes (22–72), P  < 0.01. However, procedural success (87%, 90%, 85%, P  = 0.1), technical success (89%, 91%, 88%, P  = 0.24), and complications rates (2.8%, 2.5%, 2.2%, P  = 0.88) were not different. Conclusions: The most common target vessel location for CTO PCI is the proximal coronary segment. PCI of proximal occlusions is associated with adverse clinical and angiographic characteristics and often requires use of the retrograde approach, but can be accomplished with high procedural and technical success and low complication rates. © 2016 Wiley Periodicals, Inc.